Motif Indonesia dalam Perjanjian Indonesia-United Arab Emirates Comprehensive Economic Partnership Agreement - Bagus Ghufran Satriaaji; Asra Virgianita (Intermestic: Journal of International Studies, 2025)
This study examines Indonesia’s motives in establishing a cross-regional economic partnership with the United Arab Emirates through the IUAE-CEPA. Departing from Indonesia’s typical trade strategy focused on large or geographically proximate economies, this agreement reflects a shift in economic diplomacy. Applying cross-regional trade agreement partner selection theory and a qualitative document analysis method, the research reveals that Indonesia’s motivations extend beyond economic interests to include political and diplomatic strategy. The findings contribute to understanding how emerging economies leverage trade agreements for geopolitical positioning and regional economic integration.